The Influence of Obesity on the Infection Risk of Prosthetic Joint Infection in the Geriatric Orthopedic Population. (4th October 2017) - Nocon, Allina; Henry, Michael; Russell, Celeste; Westrich, Geoffrey; Brause, Barry; Miller, Andy
Abstract: Background: Prosthetic joint infection (PJI) is a dreaded complication of arthroplasty. PJI are more common in the elderly and are associated with a substantial increase in 5-year mortality risk. PJI risk may correlate with increasing body mass index (BMI). However, the effect of BMI on PJI risk in the elderly has not been evaluated, to our knowledge. We sought to evaluate this relationship in a cohort of geriatric arthroplasty patients at an orthopedic specialty hospital. Methods: A retrospective cohort of hip and knee arthroplasty patients (age >75) from 2009–2014 was identified through administrative hospital data using ICD-9 codes. Patients with a BMI <14 or >60 kg/m 2, height <142 or >200 cm, and weight <36 or >226 kg were excluded. The presence of infection was confirmed via chart review; all PJIs met MSIS criteria. Obesity was defined as having a BMI >30. Univariate analyses were done using χ 2 tests and adjusted models were assessed using logistic regression. Results: 13, 755 geriatric arthroplasty patients (6, 408 total hip arthroplasties [THA] and 7, 347 total hip arthroplasties [TKA]) were assessed. Mean age and BMI were 82 (±5.4) and 28.1 (±5.3), respectively. In an unadjusted model, obesity was associated with infection in THA ( P = 0.02), but not TKA ( P = 0.31). This association remained after adjusting for age, sex, and diabetes. Obesity was associated with an increased risk of infection in THA [OR=1.89 (95% CI 1.12–3.21); P = 0.02]. However, as with the unadjusted model, this relationship was not found in TKA ( P =  0.50). Conclusion: Obesity increases THR PJI risk in the elderly. However, no such association was found for TKA. Future studies are needed to quantify the compounded risk of obesity in the geriatric arthroplasty patient. Disclosures: All authors: No reported disclosures.